2010
DOI: 10.1590/s0104-11692010000200013
|View full text |Cite
|
Sign up to set email alerts
|

Patient Destination after Discharge from Intensive Care Units: Wards or Intermediate Care Units?

Abstract: This study characterizes patients hospitalized in Intensive Care Units (ICUs) Destino del paciente después de recibir el alta médica de la unidad de cuidados intensivos: ¿unidad de internación o intermedia?Este estudio tuvo como objetivos caracterizar a los pacientes internados en unidades de terapia intensiva (UTI) de hospitales con unidades intermediarias -en lo que se refiere a los datos demográficos y clínicos -e identificar los factores relacionados con el alta médica para esa unidad. Es estudio prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 13 publications
(8 reference statements)
0
9
0
2
Order By: Relevance
“…The NAS average was 71.3%, a value that is higher than the value found in most studies that applied this instrument to patients admitted to general ICUs [5], [6], [23], [24], [25]. Two investigations, conducted in Brazil, addressed specific populations and found NAS means that were higher: 72.93% in the analysis of elderly patients [7] and 73.6% in a postoperative cardiac surgery unit [26].…”
Section: Discussionmentioning
confidence: 73%
“…The NAS average was 71.3%, a value that is higher than the value found in most studies that applied this instrument to patients admitted to general ICUs [5], [6], [23], [24], [25]. Two investigations, conducted in Brazil, addressed specific populations and found NAS means that were higher: 72.93% in the analysis of elderly patients [7] and 73.6% in a postoperative cardiac surgery unit [26].…”
Section: Discussionmentioning
confidence: 73%
“…Other studies have previously shown the need for intermediate care units for patients who suffer from a critical disease as an additional step before sending such patients to a conventional ward. The workload results at discharge in this group of patients again reveal the usefulness of units for patients requiring high-intensity care but low-intensity medical treatment (16)(17) .…”
Section: Rev Esc Enfermmentioning
confidence: 75%
“…These patients, however, may require a heavy workload (13) , which in turn overloads the professionals in these sectors as they meet the care demands of these patients. This is a fact that requires greater investigation because imbalance in the proportion between patients and nurses has important implications for the safety of patients, for hospital mortality and morbidity, professionals turnover, and for different aspects related to the health of workers such as the occurrence of burnout syndrome and professional dissatisfaction (14) .…”
Section: Introductionmentioning
confidence: 99%